Recent advances in the science of human milk oligosaccharides - Tadasu Urashima; Katsumi Ajisaka; Tetsuro Ujihara; Eri Nakazaki (BBA Advances)
Human colostrum and mature milk contain oligosaccharides (Os), designated as human milk oligosaccharides (HMOs). Approximately 200 varieties of HMOs have been characterized.Although HMOs are not utilized as an energy source by infants, they have important protective functions, including pathogenic bacteria and viral infection inhibitors and immune modulators, among other functions, and HMOs stimulate brain-nerve development. The Os concentration is average 11 g/L in human milk but >100 mg/L in mature bovine milk, which is used to manufacture infant formula, suggesting that human-identical milk oligosaccharides (HiMOs) should be incorporated into milk substitutes. Some infant formulas incorporating 2′-fucosyllactose and lacto-N-neotetraose are now commercially available, and intervention trials have been concluded.We review basic HMO information, including their chemical structures and concentrations, attempts to synthesize HMOs at small and plant scale, studies that clarified HMO biological functions, and interventions with milk substitutes incorporating HiMOs in formula-fed infants.